Electrocochleographic recording in Asian adults: Preliminary normative data and demographic analyses - Zakaria, Mohd Normani; Nik Othman, Nik Adilah; Musa, Zalilah (Elsevier, 2017)
Objective: Electrocochleography (ECochG) is valuable to diagnose Meniere's disease objectively. The aim of the present study was to provide preliminary normative data for ECochG among Asian adults. The influences of ethnicity (Malay versus Chinese) and gender on ECochG results were also studied. Methods: Twenty-two Malay adults (10 men and 12 women) and twenty Chinese participants (10 men and 10 women) aged between 20 and 49 years participated in this study. Extratympanic ECochG (ET-ECochG) was recorded according to standard non-invasive procedure. Summating potential (SP) amplitude, action potential (AP) amplitude and SP/AP ratio were analyzed accordingly. Results: ET-ECochG results were found to be comparable between left and right ears (p > 0.05). No notable differences in ET-ECochG results were found between Malay and Chinese groups (p > 0.05). No significant influence of gender on ET-ECochG outcomes was also noted (p > 0.05). The derived normative data for Asian adults (84 ears) are consistent with previous reports. Conclusion: The present study provides preliminary normative data for ET-ECochG among Asian adults. The ECochG components do not appear to be influenced by either ethnicity or gender. The derived normative data can be used for clinical applications and as the reference for future studies involving Asian population.